THE IMPORTANCE OF HOSPITAL COMMITTEES IN QUALITY MANAGEMENT, PATIENT SAFETY, AND STANDARDIZATION OF HEALTHCARE PRACTICES (CIPEEX, 2025)
INTRODUCTION: Hospital committees are multidisciplinary groups that enhance quality and safety in healthcare, standardizing practices, preventing risks, and promoting effective patient care. OBJECTIVE: To review the literature in order to assess the importance of hospital committees in improving healthcare, their role in patient safety, in the efficient use of resources, and in the standardization of practices. METHODS: The study was conducted through a descriptive and exploratory literature review, with a qualitative approach. The search for materials was conducted in scientific databases, using the term "hospital committees" as the exclusive descriptor. Recent articles and documents, in Portuguese and English, that addressed the structure, functions, and relevance of these committees in the hospital context were selected. Understanding their role is essential to improving hospital organization and ensuring better care outcomes. RESULTS: The included studies showed that the combination of systematized actions and evaluation indicators improves hospital management in several public institutions. Some studies reported improvements in the processes and services offered, a reduced need for corrective interventions, a lower prevalence of patient safety failures, and a significant contribution to organizational effectiveness. CONCLUSION: According to the research participants, hospital committees are essential for institutional management, contributing to policy formulation, coordination, and service monitoring. They operate in an organized manner, with a sufficient number of members, adequate physical structure, and a defined legal basis. These committees produce key indicators for hospital quality, which are used to monitor goals and limits. By making this information available to management and society, they promote transparency and strengthen the management of healthcare services.